Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Jurusan Akuntansi Berkarir Di Bidang Perpajakan - anugrah muzialani lani; Desi Handayani; Novrina Chandra (Politeknik Caltex Riau, 2022)
This study aims to determine the positive influence of motivation, professional recognition and perception on the interest of students majoring in accounting for a career in taxation. The population in this study were students of the Department of Accounting, Padang State Polytechnic and Andalas University who had studied taxation courses and the number of samples was 280 respondents. The method in this research is quantitative. The data used is primary data obtained through distributing questionnaires in the form of google form and measured using a Likert scale. The data processing program uses the Statictical Product and Service Solution (SPSS) version 18 program. The results show that motivation has a positive effect on student interest in accounting for a career in taxation, professional recognition has a positive effect on student interest in accounting for a career in taxation, perception has a positive effect on student interest majoring in accounting for a career in taxation. Keywords: Motivation, Professional Recognition, Perception and Interest in a Career in Taxation